ATTACHMENT TO ONE’S HOMETOWN AS A RESOURCE OF RESILIENCE DURING FULL-SCALE WAR (BASED ON INTERVIEWS FROM THE PROJECT «THOSE WHO STAYED: TESTIMONIES OF RESIDENTS OF KHARKIV AND KHARKIV REGION») - Nesterenko, Viktoriia (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
This article explores the experiences of Kharkiv residents who consciously choose to remain in the city despite the constant danger posed by the full-scale war. The source base for this research consists of oral history interviews collected between 2023 and 2025 within the framework of the project «Those Who Stayed: Testimonies of Residents of Kharkiv and Kharkiv Region», supported by the Center for Urban History of East Central Europe. The aim of the study is to identify the arguments residents use to justify their decision to stay, examine how attachment to their hometown is articulated in oral testimonies, and analyze how this attachment contributes to the formation of psychological and social resilience during wartime. The oral history approach, combined with thematic analysis, reveals key motivations behind the decision to stay: a sense of duty, identification with the city, emotional attachment, and memory of the urban environment as both a personal and collective resource. Despite the loss of infrastructure and social ties, the city itself, its familiar streets, architectural landmarks, and landscapes, takes on the role of a supportive agent. The study seeks to deepen our understanding of urban resilience through the lens of individual wartime experiences. Respondents emphasize their connection to the city—whether through birth, long-term residence, or emotional ties. The loss of social capital due to evacuation is often offset by the city’s physical and social environment. In the narratives, Kharkiv appears not just as a geographic location, but as a social resource that sustains resilience. The urban experience is compared to that of rural residents, whose adaptation to war followed a different trajectory. Motivations to remain or return include care for relatives, a desire to be useful, and the need to preserve identity and a sense of belonging to the homeland. The article also highlights the paradox in which the threat of war is perceived as less stressful than the experience of displacement and living in unfamiliar environments away from one’s native city.